INTERPRETATION OF THE CONCEPT OF PRAGMATICS IN MODERN FOREIGN AND NATIONAL STUDIES (TAMADDUN NURI JURNALI, 2024)
This article emphasisez on pragmatics in modern and traditional studies as well as given several notions concerning interpretation of the concept of pragmatics from prominent linguists who contributed in this sphere.